Experimental and numerical study on the performance of hollow and concrete‐filled elliptical steel columns subjected to severe fire. (3rd August 2015) - Ali, Faris; Nadjai, Ali; Goodfellow, N.
Summary: This paper presents the results of an experimental and validated theoretical study to investigate the performance of steel columns with hollow and concrete‐filled elliptical sections subjected to hydrocarbon fire. The test programme involved 18 columns with 200 × 100 × 8‐mm, 300 × 150 × 8‐mm and 400 × 200 × 8‐mm elliptical sections representing slenderness of 50, 33 and 24, respectively. The 1800‐mm columns were subjected to the severe hydrocarbon fire curve and tested under loadings ratios of 20%, 40% and 60% of the EC3 ultimate strength. The paper presents the obtained experimental results including measured axial and lateral displacements, failure temperatures and failure time. A three‐dimensional model was built using the finite element method (FEM) and was validated using the obtained tests results. The finite element model showed an excellent agreement with tests results of failure temperatures, failure modes, and axial and lateral displacements. However, because of restrictions in the software capabilities, the mechanical–thermal behaviour of concrete including spalling was not considered in the model. The verified finite element model was used to conduct a parametric analysis involving a range of parameters of loading level and slenderness. The study has shown that the concrete‐filled sections have demonstrated an improved fire resistance when compared with the hollow sections under the low loading ratios. The FEM model has successfully predicted the unique thermal profile of elliptical section under fire, which was observed during the tests. Copyright © 2015 John Wiley & Sons, Ltd.